Answer:
(7x+6y) is a binomial factor of the given expression ![49x^2+84xy+36y^2](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2)
Therefore ![49x^2+84xy+36y^2=(7x+6y)(7x+6y)](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2%3D%287x%2B6y%29%287x%2B6y%29)
Step-by-step explanation:
Given expression is ![49x^2+84xy+36y^2](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2)
To find the binomial factor :
![49x^2+84xy+36y^2](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2)
Rewritting the above expression as
![=7^2x^2+2(7)(6)xy+6^2y^2](https://tex.z-dn.net/?f=%3D7%5E2x%5E2%2B2%287%29%286%29xy%2B6%5E2y%5E2)
![=(7x)^2+2(7x)(6y)+(6y)^2](https://tex.z-dn.net/?f=%3D%287x%29%5E2%2B2%287x%29%286y%29%2B%286y%29%5E2)
( using the formula
here a=7x and y=6y )
( using the formula
)
Therefore ![49x^2+84xy+36y^2=(7x+6y)(7x+6y)](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2%3D%287x%2B6y%29%287x%2B6y%29)
(7x+6y) is a binomial factor of the given expression ![49x^2+84xy+36y^2](https://tex.z-dn.net/?f=49x%5E2%2B84xy%2B36y%5E2)
7/10 of 80 is 56
4/5 of 80 is 64
3/4 of 80 is 60
5/8 of 80 is 50
1/2 of 80 is 40
1/4 of 80 is 20
1/10 of 80 is 8
1/8 of 80 is 10
to work these out divide the number by the denominator (bottom number) and multiply by the numerator (top number)
Answer:
It would be 8 years ago.
Step-by-step explanation:
-First, subtract $14.35 from $16.35, which gives you 2.
-Next, remember that $0.25 is a quarter, so how many quarters make $2?
-0.25x4 gives you a dollar, so 0.25x8 gives you 2 dollars.
Hope it helps!
The building blocks of proteins are amino acids.
Answer:
see explanation
Step-by-step explanation:
Given
![\sqrt{\frac{4x^2}{3y} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B4x%5E2%7D%7B3y%7D%20%7D)
= ![\frac{\sqrt{4x^2} }{\sqrt{3y} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B4x%5E2%7D%20%7D%7B%5Csqrt%7B3y%7D%20%7D)
= ![\frac{2x}{\sqrt{3y} }](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B%5Csqrt%7B3y%7D%20%7D)
Rationalise the denominator by multiplying the numerator/ denominator by ![\sqrt{3y}](https://tex.z-dn.net/?f=%5Csqrt%7B3y%7D)
Note that
×
= a
=
× ![\frac{\sqrt{3y} }{\sqrt{3y} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B3y%7D%20%7D%7B%5Csqrt%7B3y%7D%20%7D)
= ![\frac{2x\sqrt{3y} }{3y}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%5Csqrt%7B3y%7D%20%7D%7B3y%7D)